Bramwell's helicopter dynamics - Bramwell, A. R. S. (American Institute of Aeronautics and Astronautics ; Butterworth-Heinemann, 2001)
Since the original publication of 'Bramwell's Helicopter Dynamics' in 1976, this book has become the definitive text on helicopter dynamics and a fundamental part of the study of the behaviour of helicopters. This new edition builds on the strengths of the original and hence the approach of the first edition is retained. The authors provide a comprehensive overview of helicopter aerodynamics, stability, control, structural dynamics, vibration, aeroelastic and aeromechanical stability. As such, Bramwell's Helicopter Dynamics is essential for all those in aeronautical engineering. THE single volume comprehensive guide for anyone working with helicopters Written by leading worldwide experts in the field.